The Future of AI in Mental Health: A Professional and Academic Outlook - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Future of AI in Mental Health: A Professional and Academic Outlook The global mental health crisis, characterized by rising prevalence rates and sig...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning